Pathologic Characteristics of Spitz Melanoma With MAP3K8 Fusion or Truncation in a Pediatric Cohort. (December 2019) - Newman, Scott; Pappo, Alberto; Raimondi, Susana; Zhang, Jinghui; Barnhill, Raymond; Bahrami, Armita
Abstract : Spitz melanoma is a rare variant of melanoma defined by distinct clinical, histologic, and genetic features and affecting patients of all ages. Half of these tumors are driven by fusion of kinase genes including ALK, NTRK1/3, ROS1, RET, MET, or BRAF . We recently reported recurrent fusion or truncation of the potentially targetable serine-threonine kinase gene MAP3K8 in 33% of Spitz melanomas. Here we describe the histologic features of these MAP3K8 -rearranged tumors (16 pediatric Spitz melanomas; 1 atypical Spitz tumor), using hematoxylin-eosin slides, p16 immunohistochemistry, and CDKN2A fluorescence in situ hybridization. The lesions consisted of a compound melanocytic proliferation, ranging in thickness from 1.5 to 13.4 mm (median, 3.1 mm), with 8 having a predominant dermal and 3 having a predominant junctional component. The predominant cell type was epithelioid (94%). The epithelioid melanocytes were generally monomorphic and amelanotic, arranged in expansile epithelial aggregates, confluent hypercellular nests, or enlarged syncytial nodules in the dermis. Ulceration was present in 9 of 17 tumors (53%) and deep mitotic figures were seen in 15 of 17 tumors (88%). Complete loss of p16 expression and homozygous CDKN2A deletion were observed in 82% and 70% of tumors, respectively. Recognition of MAP3K8 -altered Spitz melanoma may thus be facilitated by these morphologic features, most notably presence of cohesive cellular nodules in the dermis and an epithelioid-cell phenotype.